Feed bunk management effects steer performance and behaviour - Della Rosa, Maria Milagros; Toffaletti, Jose Rodolfo; Aello, Mario; Burges, Julio Cesar (CSIRO, 2020)
Animal performance and behaviour in fattening steers using ad libitum or restricted feed-bunk management were evaluated. High store-capacity self-feeders with weekly recharge were used in ad libitum management (ADLIB), while manual twice-a-day delivery was used in restricted management (REST). Twenty-four steers were allotted to 12 pens and fed with a high corn-grain diet without roughage, and randomly assigned to one of the treatments. Animal behaviour was recorded every 5 min throughout 24 h for 3 days. No bunk-management effect was evident in bodyweight (P 0.95) or average daily gain (P = 0.91). Even though ADLIB resulted in higher dry-matter intake (P = 0.03), the animals spent less time per day eating feed than did those under REST (P < 0.01), with more eating sessions per day (P = 0.02), which were shorter (P = 0.06). Rumination time was greater (P = 0.07) under ADLIB than under REST, while the opposite was observed for time spent eating (P < 0.01). Resting time was longer in animals under ADLIB (P = 0.02), with more sessions per day (P = 0.06), than under REST. In conclusion, the two feed-bunk managements evaluated had no negative implications either for animal performance or behaviour.